2022
DOI: 10.5194/gchron-4-435-2022
|View full text |Cite
|
Sign up to set email alerts
|

Cosmogenic nuclide and solute flux data from central Cuban rivers emphasize the importance of both physical and chemical mass loss from tropical landscapes

Abstract: Abstract. We use 25 new measurements of in situ produced cosmogenic 26Al and 10Be in river sand, paired with estimates of dissolved load flux in river water, to characterize the processes and pace of landscape change in central Cuba. Long-term erosion rates inferred from 10Be concentrations in quartz extracted from central Cuban river sand range from 3.4–189 Mg km−2 yr−1 (mean 59, median 45). Dissolved loads (10–176 Mg km−2 yr−1; mean 92, median 97), calculated from stream solute concentrations and modeled run… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 88 publications
0
5
2
Order By: Relevance
“…We calculate a chemical weathering flux of 113 (50-194) t km À2 year À1 for that year, suggesting chemical denudation rates of 42 (19-72) mm kyr À1 when assuming that weathering is not iso-volumetric (Text S1.4). These values for the central highlands of Madagascar are in the range of the estimates obtained by Campbell et al (2022) but higher than the rates obtained for Sri Lanka. Even though this estimate entails large uncertainties, it suggests that mass loss through chemical weathering is probably a major (and hitherto unacknowledged) factor for regional denudation in Madagascar.…”
Section: The Importance Of Deep Chemical Weatheringcontrasting
confidence: 58%
See 3 more Smart Citations
“…We calculate a chemical weathering flux of 113 (50-194) t km À2 year À1 for that year, suggesting chemical denudation rates of 42 (19-72) mm kyr À1 when assuming that weathering is not iso-volumetric (Text S1.4). These values for the central highlands of Madagascar are in the range of the estimates obtained by Campbell et al (2022) but higher than the rates obtained for Sri Lanka. Even though this estimate entails large uncertainties, it suggests that mass loss through chemical weathering is probably a major (and hitherto unacknowledged) factor for regional denudation in Madagascar.…”
Section: The Importance Of Deep Chemical Weatheringcontrasting
confidence: 58%
“…(2016) estimated that deep chemical weathering accounts for 60% of the total denudation in a thick, highly weathered, regolith on the Cameroon craton. A recent study from Cuba furthermore indicated significant landscape‐scale mass loss that was not reflected in in situ 10 Be cosmogenic nuclide measurements (4–180 t km −2 year −1 corresponding to 2–69 mm kyr −1 when ρ = 2.6 t m 3 ), with rock dissolution rates (24–154 t km −2 year −1 corresponding to 9–59 mm kyr −1 when ρ = 2.6 t m 3 ) exceeding the latter in 15 of 22 basins (Campbell et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basin‐averaged erosion rate estimates from TCNs use an idealized model of erosional processes, which requires a set of assumptions to be fulfilled (Granger et al., 2001; Von Blanckenburg, 2005). However, in extreme environments, such as the Atacama Desert, some of these assumptions might be violated, which, however, can be identified using paired cosmogenic nuclides (Campbell et al., 2022). The following section will consider the sensitivity of TCN‐derived erosion rates to processes particular to hyperarid environments.…”
Section: Interpretation and Discussionmentioning
confidence: 99%